Concurrent determination of nanocrystal shape and amorphous phases in complex materials by diffraction scattering computed tomography. Issue 1 (27th January 2017) - Birkbak, Mie Elholm; Nielsen, Ida Gjerlevsen; Frølich, Simon; Stock, Stuart R.; Kenesei, Peter; Almer, Jonathan D.; Birkedal, Henrik
Abstract : The size and size anisotropy of nanocrystals is determined together with the distribution of amorphous phases inside a seven‐capillary model reactor filled with various nanomaterials. This is achieved by diffraction scattering computed tomography followed by Rietveld refinement and multivariate analysis of Rietveld backgrounds. Abstract : Advanced functional materials often contain multiple phases which are (nano)crystalline and/or amorphous. The spatial distribution of these phases and their properties, including nanocrystallite size and shape, often drives material function yet is difficult to obtain with current experimental techniques. This article describes the use of diffraction scattering computed tomography, which maps wide‐angle scattering information onto sample space, to address this challenge. The wide‐angle scattering signal contains information on both (nano)crystalline and amorphous phases. Rietveld refinement of reconstructed diffraction patterns is employed to determine anisotropic nanocrystal shapes. The background signal from refinements is used to identify contributing amorphous phases through multivariate curve resolution. Thus it is demonstrated that reciprocal space analysis in combination with diffraction scattering computed tomography is a very powerful tool for the complete analysis of complex multiphase materials such as energy devices.